2023
DOI: 10.1002/aelm.202201309
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characteristics of Transferrable Single‐Crystalline AlN Nanomembranes

Abstract: Single‐crystalline inorganic semiconductor nanomembranes (NMs) have attracted great attention over the last decade, which poses great advantages to complex device integration. Applications in heterogeneous electronics and flexible electronics have been demonstrated with various semiconductor nanomembranes. Single‐crystalline aluminum nitride (AlN), as an ultrawide‐bandgap semiconductor with great potential in applications such as high‐power electronics has not been demonstrated in its NM forms. This very first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 94 publications
1
5
0
Order By: Relevance
“…Overall, combining the discussion from this work with our previous studies, 43,45,61 the charge compensation phenomenon observed on the Ga-polar GaN surface can be a mixture of multiple effects.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Overall, combining the discussion from this work with our previous studies, 43,45,61 the charge compensation phenomenon observed on the Ga-polar GaN surface can be a mixture of multiple effects.…”
supporting
confidence: 72%
“…The uncertainty of qψ S values was estimated to be 0.09 eV by the same method from our previous work. [43][44][45] Because of the strong distortion of the GaN valence band spectra from O 2 plasma, the qf S,GaN and surface bandbending values of the treated samples C and D were calculated by linear fitting around the VBM with a Gaussian broadening uncertainty of 0.2 eV 61 (Fig. S3 in the supplementary material).…”
Section: Resultsmentioning
confidence: 99%
“…the Si and the β-Ga2O3. The role of the interface SiGaOx has served the identical roles in other grafted heterostructures where an ultrathin Al2O3 layer was applied using atomic layer deposition (ALD) [45,[54][55][56][57][58][59][60][61]. surface conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Various organoaluminum compounds with C,N-chelating ligands have been prepared for the purpose of bonding to aluminum atoms via Al-C covalent bonds and Al-N dative bonds [2][3][4][5][6][7][8][9][10][11][12]. Recently, interest in aluminum nitride (AlN) [13], a form in which aluminum and nitrogen are combined, has been on the rise due to AlN being one of the few materials with both a wide direct bandgap and large thermal conductivity [14][15][16][17][18][19][20]. Group 13 metal nitrides are commonly used in optoelectronics [21][22][23][24][25][26], as well as in high-power and high-frequency electronics [27][28][29][30][31], owing to their small atomic mass, strong interatomic bonds, and simple crystal structure [32].…”
Section: Introductionmentioning
confidence: 99%